BIOASSAY FOR THE STUDY OF ANTIBIOSIS IN Brachiaria spp. ON THE SPITTLEBUG, Aeneolamia varia (Fabricius) (Homoptera: Cercopidae) - SOTELO, GUILLERMO; LAPOINTE, STEPHEN L.; SERRANO, MIGUEL S. (Revista Colombiana de Entomología, 1993)
A new feeding system for rearing cercopids on accessions of Brachiaria spp. was developed to study the effect of substances supplied to the plant roots in a hydroponic arrangement. The system consisted of a mylar cylinder inserted into a polycarbonate test tube. The mylar cylinder enclosed the root system of a grass plant and provided a feeding chamber for the cercopid nymphs. The system developed resulted in excellent survival, development time, and dry weight of adults of A. varia compared with A. varia reared on susceptible accessions of Brachiaria spp. in a glasshouse. It was demonstrated that the cercopid can ingest substances translocated by the plant xylem. Ecdysone (20-hydroxyecdisone) was administered in solution to the roots of B. ruziziensis CIAT 654. At 50 ppm, ecdysone stimulated the molt of IV instar nymphs within 24 hours. At 100 ppm, ecdysone caused the death of all nymphs and several were malformed. Juvenile hormone (JH-I II) at 100 ppm did not have a significant effect on the development of A. varia.